Boris Gasparov Speech, memory, and meaning. Intertextuality in everyday language - Becerra Merino, Jennifer Carolina (Lenguas Modernas, 2013)
Berlin/New York, Walter De Gruyter Mouton 2010, 316 páginas ISBN: 978-3-11-021910-4